2016
DOI: 10.3389/fphys.2015.00416
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Local Regional Hemodynamic Signal Changes during Motor Execution and Motor Imagery Using Near-Infrared Spectroscopy

Abstract: The aim of this study was to clarify the topographical localization of motor-related regional hemodynamic signal changes during motor execution (ME) and motor imagery (MI) by using near-infrared spectroscopy (NIRS), as this technique is more clinically expedient than established methods (e.g., fMRI). Twenty right-handed healthy subjects participated in this study. The experimental protocol was a blocked design consisting of 3 cycles of 20 s of task performance and 30 s of rest. The tapping sequence task was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 67 publications
4
28
0
Order By: Relevance
“…With regard to the MI task, our results are comparable with others, for instance Iso et.al . ( Iso et al, 2015 ) and Wriessnegger et al ( Wriessnegger et al, 2008 ) showed similar level of haemodynamic response to a imagery motor task from SMA and M1 respectively.…”
Section: Discussionmentioning
confidence: 75%
“…With regard to the MI task, our results are comparable with others, for instance Iso et.al . ( Iso et al, 2015 ) and Wriessnegger et al ( Wriessnegger et al, 2008 ) showed similar level of haemodynamic response to a imagery motor task from SMA and M1 respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Previous imaging studies have shown that the activity in SMA is directly related to movement output (Obrig et al, 1996 ; Christensen et al, 2000 ). It has been reported that the SMA is involved in motor preparation and is activated not only during ME, but also during the preparation and inhibition of movements (Kasess et al, 2008 ; Guillot et al, 2012 ; Iso et al, 2016 ). Some studies also suggest that MI requires a similar amount of time as the execution does (Guillot and Collet, 2005 ), implying that they are produced through the analogous computational steps in the brain (HĂŠtu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the authors were further able to show that, by solely studying HbO changes, motor imagery could be used to correctly classify a user’s intent ~80% of the time. Other types of motor imagery paradigms that have established significant hemodynamic signal changes with fNIRS include tennis arm-swinging motion ( 80 ) and a finger tapping sequence ( 81 ).…”
Section: Motor Imagery Paradigms With Fnirsmentioning
confidence: 99%